(untitled) (Jurnal Peternakan Lingkungan Tropis, 2023)
This research aimed to determine the level of farmer’s knowledge regarding livestock management, specifically the distance between cowsheds and settlements, and to understand the perceptions of residents living within a maximum radius of 250 meters from the farm. Respondents were required to have a minimum of 10 cattle in the farm. The study found that the level of knowledge of farmers at Aufa Wijaya Farm regarding the distance between cowshed and settlements was high, as evaluated from their understanding of the minimum distance between cowshed and the settlement, cowshed construction, and the impact of livestock waste. Moreover, the study revealed that the perception of the community living within the cattle farm’s radius was not significantly affected. This is attributed to the positive economic impact brought by the farm, such as job opportunities, as well as positive social aspects. During the Idul Adha feast, Aufa Wijaya Farm conducts animal sacrifices and distributes the meat evenly to the surrounding community.